STUDI KELAYAKAN INVESTASI PROYEK PENGEMBANGAN KAWASAN PERUMAHAN THE APEL BIRU HILL SAMARINDA - ADITIA PRATAMA, HOLIS (KURVA S JURNAL MAHASISWA, 2014)
Residences is a basic human needs. The growth rate of human resulted in high demand for residences. The magnitude of this business opportunity make the developers competing to develop a residential area in samarinda city. To develop residential area required considerable funds.The Apel Biru Hill Residence is one of residences which growing in samarinda city. This residence is developing house type 45 and 32 for the project phase 1. To know the project is feasible and profitable to be implemented, is necessary to do feasibility study investment of financial terms. Determining the investment feasibility in this study, using the NPV (Net Present Value), IRR (Internal Rate of Return), and PI (Profitability Index) method.From the research result that development project of The Apel Biru Hill residence feasible and profitable to be implemented with NPV ( Net Present Value ) give a positive value as big as Rp. 8.475.248.752,91 , IRR ( Internal Rate of Return ) 11,754 % greater i at the desired rate of return ( IRR > 11 % ) , PI ( Profitability Index ) 1,696 and greater than hinted that PI > 1.